High-Efficiency Dual-Band 8-Port MIMO Antenna Array for Enhanced 5G Smartphone Communications - Feng, Hongzhi (Journal of Artificial Intelligence and Information, 2024)
The study presents the design and analysis of a dual-band 8-port MIMO antenna array for 5G smartphone applications. The proposed antenna operates in the 3.30–3.65 GHz and 5.25–5.85 GHz bands, covering key sub-6 GHz frequencies for 5G communication. The antenna array employs inverted L-shaped monopole elements and a defected ground structure (DGS) to achieve efficient radiation performance and strong isolation between elements. Simulation and measurement results show that the antenna array achieves a return loss better than -25 dB across both frequency bands, with mutual coupling reduced to below -15 dB. The system demonstrates total efficiencies of over 75% at 3.5 GHz and 65% at 5.5 GHz, making it well-suited for high-efficiency MIMO systems. The antenna's compact design and high performance make it a strong candidate for integration into future 5G smartphones, supporting reliable, high-speed communication.